BEYOND RESEARCH COOPERATION ON SUCCESSFUL AGING: COMPARATIVE ANALYSIS OF THE COGNITIVE PERFORMANCE OF ELDERLY PEOPLE IN BRAZIL AND FINLAND - Santos, Geraldine Alves dos; Sanerma, Päivi (Revista Prâksis, 2019)
ABSTRACT Many studies have been carried out, mainly in the last decades, to understand the normal and pathological process of aging in the different areas of knowledge. However, many gaps still remain in the progress of science. In this sense, the overall objective of the present study was to evaluate the comparison between the performance of congruent elderly people in Brazil and Finland. The study method had a quantitative, descriptive cross - sectional design. The sample consisted of 194 subjects of both sexes, aged between 60 and 79 years, residing in the municipality of Ivoti / Rio Grande do Sul / Brazil and 93 subjects, both genders aged 65 to 85 years residing in Riihimäki / Finland. The instrument used was the Mini Mental State Examination (MMSE). Data were analyzed statistically in SPSS version 25.0 through descriptive analysis of frequency and comparison of means by the Mann Whitney test (p≤0.05). The results showed that the cognitive performance of elderly people in the Ivoti group was significantly higher than those of Riihimäki. It can be concluded that cultural variables influenced outcomes, such as experiences in the early stages of human development and current interpersonal relationships. Keywords: Cognitive performance. Successful aging. Elderly. RESUMO Muitos estudos têm sido realizados, principalmente nas últimas décadas, para compreender o processo normal e patológico de envelhecimento, nas diferentes áreas do conhecimento. Entretanto, muitas lacunas ainda se mantêm presentes no progresso da ciência. Neste sentido, o objetivo geral do presente estudo foi avaliar a comparação entre o desemepnho congitivo de pessoas idosas residentes no Brasil e na Finlândia. O método do estudo teve um delineamento quantitativo, descritivo e transversal. A amostra compreendeu 194 sujeitos, de ambos os sexos, com idade entre 60 e 79 anos, residentes no município de Ivoti/Rio Grande do Sul/Brasil e 93 sujeitos, de ambos os sexos com idade entre 65 e 85 anos residentes em Riihimäki/Finlândia. O instrumento utilizado foi o Mini Exame do Estado Mental (MEEM). Os dados foram analisados estatisticamente no programa SPSS versão 25.0 através de análises descritivas de frequência e de comparação de médias pelo teste Mann Whitney (p≤0,05). Os resultados demonstraram que o desempenho cognitivo das pessoas idosas do grupo de Ivoti foi significativamente maior que os de Riihimäki. Pode-se concluir que variáveis culturais influenciaram os resultados, tais como experiências nas fases iniciais do desenvolvimento humano e as relações interpessoais atuais. Palavras-chave: Desempenho cognitivo. Velhice. Idosos.